2016
DOI: 10.2106/jbjs.rvw.o.00057
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Tibial Slope: Effect on, and Interaction with, Knee Kinematics

Abstract: Posterior tibial slope should be measured on a long lateral or an expanded lateral radiograph. Posterior tibial slope decreases the quadriceps force needed to exert knee extension moment. Posterior tibial slope parallel to natural tibial slope minimizes tibial component subsidence. Posterior tibial slope should be increased rather than releasing the posterior cruciate ligament (PCL) to restore normal kinematics in a knee that is tight in flexion. Larger tibial slope widens the flexion gap in posterior stabiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…Due to a large anatomical variability of the tibia, conventional precontoured plates often don’t adequately fit. As consequence, inadequate reductions and/or fixation can lead to malalignment and incongruity of the joint surface, and biomechanical and functional problems 23,27,28 . Correctly addressing tibial fractures is therefore increasingly accepted as an important prognostic factor for functional outcome 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Due to a large anatomical variability of the tibia, conventional precontoured plates often don’t adequately fit. As consequence, inadequate reductions and/or fixation can lead to malalignment and incongruity of the joint surface, and biomechanical and functional problems 23,27,28 . Correctly addressing tibial fractures is therefore increasingly accepted as an important prognostic factor for functional outcome 5 .…”
Section: Discussionmentioning
confidence: 99%
“…So, in our opinion, both sides' fracture pattern and patient's age suggested prosthetic replacement rather than osteosynthesis. Also, moderate EOA was present on the right side, and mild EOA on the left side; according to recent literature [[10], [11], [12], [13],23,24,[26], [27], [28]], RSA seems to improve clinical results with a better function over HA when poor potential for tuberosity healing is present (comminuted tuberosities, osteoporotic bone), also in mild or absent EOA. Lastly, treatment of concomitant bilateral proximal humeral fracture should rely on the same principles as for monolateral injury.…”
Section: Case Presentationmentioning
confidence: 79%
“…If surgical treatment is chosen, pre-operative planning should take into account Hertel's criteria [9] to predict the risk of humeral head avascular necrosis (AVN) and subsequent need for revision surgery in case of osteosynthesis. An increasing number of Authors suggest reverse shoulder arthroplasty (RSA) as a valid option instead of hemiarthroplasty (HA) or open reduction and internal fixation (ORIF) for the treatment of displaced fractures of humeral head in this population [[10], [11], [12], [13]], and a multicenter combined randomized controlled and observational trial on this issue has started [14]. In the rare situation of simultaneous bilateral proximal humeral fracture, choice of treatment is still more controversial, and it can vary from conservative management [15] to closed reduction and percutaneous fixation [16] to ORIF of one or both sides [17], to HA of one side associated to conservative treatment [18] or ORIF [5,18] or osteochondral autograft [19] of the contralateral side, to even bilateral HA [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Accuracy of TS measurements also may be influenced by incorrect assessment of the tibial axis. 18 Faschingbauer et al 19 showed TS is most accurately measured with long lateral knee radiographs (defined as 16-20 cm of proximal tibia in view) and short view radiographs may overestimate TS by approximately 3 . The average length of the tibia in view in the current study was 17.4 and 14.9 cm in the skeletally mature and skeletally immature groups, respectively.…”
Section: Discussionmentioning
confidence: 99%